Programme Profiles and the Reform of Higher Education in Europe: The Role of Tuning Europe - Luigi F. Donà dalle Rose; Guy Haug (Universidad de Deusto, 2014)
This article provides an overview of the profiling of higher education programmes in Europe as part of the overall process of higher education reform in Europe over the past decade (2000-2012) and of the role of Tuning in this process. The article starts with a recall of the architecture and objectives of the change process, based on the interplay between the intergovernmental Bologna process (with a main focus on structural change), the European Union's parallel Agenda for the Modernisation of Higher Education (with a focus on policy change for the Union's main objectives: growth and jobs, mobility, recognition and attractiveness) and Tuning. The second part of the article provides some data about and examples of the method and importance of Tuning in stimulating and shaping the renovation of higher education programmes, with a focus on Tuning's initial geographical area (Europe) and a glimpse to other continents, in line with Europe's need to build up the visibility and attractiveness of its universities in the rest of the world. The final section is a retrospective and analytical reflection about the impact of Tuning on some key dimensions of the agenda for the modernisation of higher education in Europe; while acknowledging that the Tuning method and principles have not always been fully understood by higher education as well as governmental institutions, Tuning has made an outstanding contribution to such key aspects as the relevance, comparability and quality of programmes, the development of quality assurance and accreditation policies and agencies and the recognition of qualifications - both within Europe and with partner countries in other parts of the world.